Hanging donor lungs give good short‐, mid‐ and long‐term results in lung transplantation. Issue 1 (8th December 2019) - De Wolf, Julien; Renard, Regis; Lehouerou, Thomas; Glorion, Matthieu; Pricopi, Ciprian; Bonnette, Pierre; Parquin, Francois; Roux, Antoine; Leguen, Morgan; Chapelier, Alain; Sage, Edouard
Abstract: Background: Hanging donors are considered as marginal donors and frequently unsuitable for lung transplantation. However, there is no evidence of higher lung transplantation (LTx) morbidity‐mortality with lungs providing by hanging donor. Methods: Between January 2010 and July 2015, we performed a retrospective study at Foch hospital. We aimed to assess whether hanging donor grafts are suitable for lung transplantation. Results: A total of 299 LTx were performed. Subjects were allocated to a hanging group (HG) (n = 20) and a control group (CG) (n = 279). Donor and recipient characteristics did not differ. Primary graft dysfunction (PGD) at 72 hours was comparable in both groups ( P  = .75). The median duration of postoperative mechanical ventilation (1 [range, 0‐84] vs 1 [range, 0‐410] day, P  = .35), the hospital length of stay (31 days [20‐84] vs 32 days [12‐435], P  = .36) did not differ between the two groups. No statistically significant difference was found in 1‐year and 5‐year survival between the HG (83% and 78%) and the CG (86% and 75%), P  = .85. Conclusion: We believe that hanging donors should be considered as conventional donors with particular caution in the final evaluation of the graft and in perioperative management.